Computation of new diagonal graph Ramsey numbers - Richard M. Low; Ardak Kapbasov; Arman Kapbasov; Sergey Bereg (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2022)
For various connected simple graphs G, we extend the table of diagonal graph Ramsey numbers R(G, G) in ‘An Atlas of Graphs.’ This is accomplished by first converting the calculation of R(G, G) into a satisfiability problem in propositional logic. Mathematical arguments and scientific computing are then used to calculate R(G, G).